The Importance of Change Management in Educational Institutions - Nisak, Hernik Khoirun (Jurnal Paradigma, 2023)
Management as a science that was only recognized in the mid-19th century, management is known as the key to the success and success of managers of companies or educational institutions, both public educational institutions and Islamic educational institutions. There are even people who consider management of Islamic education as a "characteristic" of modern Islamic educational institutions, because with the management of Islamic education, educational institutions are expected to develop and succeed. Educational management is the activity of integrating educational resources so that they are focused in an effort to achieve predetermined educational goals. Meanwhile, this change also occurred in the aspect of managing school institutions. For example: management of school management, curriculum, learning process, educators and education staff, facilities and infrastructure and management of community participation and school committees. One of the responsibilities of a leader in an organization is to bring about change. Change is an absolute necessity for the development of educational institutions. Change management is the efforts made to manage the consequences caused by changes in the organization. Organizations can occur due to causes that come from within or from outside the organization. Change management is the process, tools and techniques for managing people from the change process to achieve the required results and effect change effectively within individuals, teams and the system wide.